ORIGINALITY OF COLOR IN STORIES V. PELEVIN (Neo Science Peer Reviewed Journal, 2023)
V. O. Pelevin’s prose belongs to the postmodernist movement, there are many symbolic details in it, colorism plays a special role, but the semantization of color is quite unique. This article analyzes the symbolism of color in V.O. Pelevin’s story “The Green Box”.